2017
DOI: 10.1252/jcej.16we242
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Average and Local Gas–Liquid Flow Properties in Stirred Tank Reactors with Multiple Rushton Impellers

Abstract: In this article, computational investigation of the gas-liquid ow in stirred tank with multiple Rushton impellers was carried out. Experimental results of average and local details of gas-liquid ow characters were reported, including gas-holdup, bubble Sauter diameter, speci c area and mass transfer coe cient. Thoroughly interphase momentum transfer models including drag and non-drag models were investigated, together with four mass transfer coe cient models using commercial CFD software ANSYS CFX 12.0. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ranganathan and Sivaraman found that both the slip velocity model and eddy cell model could predict the mass transfer parameter well. We have previously proven that the simulation of interface mass transfer with the eddy cell model showed the best agreement with experimentally measured data . Thus the eddy cell model was applied in this work as knormalL=KDL0.5()ϵfalse/νl0.25 where K = 0.4 is the model constant, D L is the diffusion coefficient of oxygen (2.01 × 10 −9 m 2 s −1 at 20 °C) and ϵ is the turbulence dissipation rate in the liquid phase …”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…Ranganathan and Sivaraman found that both the slip velocity model and eddy cell model could predict the mass transfer parameter well. We have previously proven that the simulation of interface mass transfer with the eddy cell model showed the best agreement with experimentally measured data . Thus the eddy cell model was applied in this work as knormalL=KDL0.5()ϵfalse/νl0.25 where K = 0.4 is the model constant, D L is the diffusion coefficient of oxygen (2.01 × 10 −9 m 2 s −1 at 20 °C) and ϵ is the turbulence dissipation rate in the liquid phase …”
Section: Methodsmentioning
confidence: 91%
“…Impeller rotation was modeled with the multi‐reference frame (MRF) . For gas–liquid flow, the interphase force, especially the drag force, plays a key role in the accurate prediction of gas distribution and further affects the prediction of mass transfer . Previously, we have demonstrated that the modified Brucato drag model showed more accurate results than other drag models such as the Grace drag model, Ishii–Zuber drag model and Tomiyama drag model .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow structure in stirred tanks is three-dimensional, complex and has high shear. The computational fluid dynamics (CFD) simulation is used to promote the study of the fundamental phenomena, which could provide the flow field information in the stirred tank [18]. As we know, the large eddy simulation (LES) could obtain the precision flow field information, and its computational consumption is between the direct numerical simulation (DNS) and the Reynolds-averaged Navier-Stokes equations (RANS) [19].…”
Section: Introductionmentioning
confidence: 99%